Blood-Brain Barrier, Blood-Brain Tumor Barrier, and Fluorescence-Guided Neurosurgical Oncology: Delivering Optical Labels to Brain Tumors - Belykh, Evgenii; Shaffer, Kurt V.; Lin, Chaoqun; Byvaltsev, Vadim A.; Preul, Mark C.; Chen, Lukui (Frontiers in Oncology, 2020)
Recent advances in maximum safe glioma resection have included the introduction of a host of visualization techniques to complement intraoperative white-light imaging of tumors. However, barriers to the effective use of these techniques within the central nervous system remain. In the healthy brain, the blood-brain barrier ensures the stability of the sensitive internal environment of the brain by protecting the active functions of the central nervous system and preventing the invasion of microorganisms and toxins. Brain tumors, however, often cause degradation and dysfunction of this barrier, resulting in a heterogeneous increase in vascular permeability throughout the tumor mass and outside it. Thus, the characteristics of both the blood-brain and blood-brain tumor barriers hinder the vascular delivery of a variety of therapeutic substances to brain tumors. Recent developments in fluorescent visualization of brain tumors offer improvements in the extent of maximal safe resection, but many of these fluorescent agents must reach the tumor via the vasculature. As a result, these fluorescence-guided resection techniques are often limited by the extent of vascular permeability in tumor regions and by the failure to stain the full volume of tumor tissue. In this review, we describe the structure and function of both the blood-brain and blood-brain tumor barriers in the context of the current state of fluorescence-guided imaging of brain tumors. We discuss features of currently used techniques for fluorescence-guided brain tumor resection, with an emphasis on their interactions with the blood-brain and blood-tumor barriers. Finally, we discuss a selection of novel preclinical techniques that have the potential to enhance the delivery of therapeutics to brain tumors in spite of the barrier properties of the brain.